EKOLOGI MEDIA DALAM PELIPUTAN KEBERAGAMAN JURNALIS TELEVISI KONTRIBUTOR AMBON - Roswita Oktavianti; Riris Loisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Media ecology reflects that mass media have to move dynamically to survive its life in the middle of media pressure and competition among other platforms. In the digital era, television as conventional media needs to embrace the technology by airing diversity issues in social media Youtube. This study has a question about media ecology in the reportage of diversity issues by television journalists in Ambon. This research using a mixed method approach, quantitative and qualitative, with content analysis, FGD, interview, and literature review as a technique for data collecting. Content analysis is conducted toward news diversity about Maluku which aired on the Youtube television channel. Then FGD is conducted further with television journalists in Ambon in which their news has been analyzed. Further, the interview is conducted with a broadcasting supervisor as well as a member of the journalist organization. This study finds that media ecology has been changing to new media ecology. Nevertheless, new media ecology is not fully implemented by television journalists in Ambon when reporting the diversity issues. The journalists will frame their news before report it mainly for news with the tendency to the SARA (ethnicity, religion, and race) issues. Framing is formed when journalists narrate their news before aired. It implemented due to their conflict experienced in the past. The journalists have responsibility and awareness in terms of the effect of their news. Their SARA’s news which aired in the Youtube platform could trigger conflict. The conflict has a huge impact on their personal and social life Ekologi media merefleksikan bahwa media massa harus bergerak dinamis untuk bertahan hidup di tengah tekanan dan kompetisi dengan berbagai platform. Di era digital, televisi sebagai media konvensional merangkul teknologi dengan menayangkan berita keberagaman di media sosial YouTube. Studi ini mengangkat tentang ekologi media dalam peliputan keberagaman jurnalis televisi kontributor Ambon. Peneliti menggunakan pendekatan penelitian campuran, kuantitatif dan kualitatif, dengan teknik pengumpulan data analisis isi, Focus Group Discussion (FGD), wawancara, dan studi pustaka. Analisis isi dilakukan pada berita-berita keberagaman di Maluku pada saluran Youtube televisi-televisi nasional. Selanjutnya dilakukan FGD dengan jurnalis televisi kontributor Ambon di mana berita-berita yang ditayangkan telah dianalisis sebelumnya. Wawancara dilakukan dengan pengawas penyiaran dan organisasi jurnalis televisi. Studi ini menemukan bahwa ekologi media beralih menjadi ekologi media baru. Namun, ekologi media baru ini tidak sepenuhnya diikuti oleh jurnalis televisi kontributor Ambon dalam melaporkan berita keberagaman. Jurnalis televisi kontributor Ambon melakukan pembingkaian ketika melaporkan berita keberagaman, khususnya berita bernuansa SARA. Pembingkaian dilakukan lebih pada narasi atau audio berita yang disajikan. Ini dilakukan karena Provinsi Maluku pernah mengalami konflik masa lalu. Jurnalis memiliki tanggung jawab dan kesadaran tinggi bahwa sejumlah peristiwa konflik terjadi salah satunya akibat berita bernuansa SARA yang tersebar luas di Youtube. Konflik tersebut telah membawa pengaruh besar dalam kehidupan pribadi dan bermasyarakat.